p-Groups with cyclic subgroup of index p and local nearrings - Raievska, M. Yu.; Інститут математики НАН України, Київ (Pidstryhach Institute for Applied Problems of Mechanics and Mathematics of NAS of Ukraine, 2024)
p-Groups with cyclic subgroup of index p as the additive groups and the multiplicative groups of local nearrings are investigated. Furthermore, the classifications of such nearrings are given.  Cite as: M. Yu. Raievska, “p-Groups with cyclic subgroup of index p and local nearrings,” Prykl. Probl. Mekh. Mat., Issue 22, 117–122 (2024), https://doi.org/10.15407/apmm2024.22.117-122